Circular Economy: A Modern Concept of Sustainable Development - Abuselidze George; Zoidze Gia (E3S Web of Conferences)
The research covers the emergence and formation of the circular economy as an independent concept and its relationship with the phenomenon of new industrialization. The paper analyses the variety of interpretations of the “circular economy” concept; The main approaches to its formation are defined. The evolutionary development of the main principles of concept formation is studied; Characteristics, current situation, and general perspectives of development are described. In addition, the article reveals the mechanisms by which a circular economy can be successfully introduced in the modern world. The difference between a linear economy and a circular economy is presented, as well as the benefits of moving to a circular economy. The conclusion provides an updated concept of circular economy and it is justified that the concept of circular economy is a universal way to form green economic growth in developing countries, which allows to overcome global economic challenges. Also, by moving from a linear economy to a circular economy, social enterprises will be able to create social good, stimulate the local economy, and create jobs by creating innovative, circular products, and maximizing the use of renewable resources and energy sources.